(untitled) (Sains Humanika, 2012)
This article attempts to discuss the issues and challenges faced by the teachers who teach Islamic education in MOE special education programme schools of deaf students in managing and assisting students in mastering the subjects of Islamic education. Disparity in many aspects than the normal student appears to have a significant impact on the achievement of Islamic education in hearing impaired students. Descriptions related to the challenges and problems faced by the teacher explained and some suggestions put forward in overcoming the situation. Hopefully this article will raise awareness and open the eyes of all parties in an effort to improve the quality of teaching and learning further improve the level of Islamic learning impaired students.